Allowance for shareholder equity: implementing a neutral corporate income tax in the European Union - Deborah Knirsch; Rainer Niemann (Arbeitskreis Quantitative Steuerlehre (arqus), 2007)
This paper proposes the introduction of a consumption-based corporate income tax in the European Union. Our proposal would guarantee neutrality regarding investment decisions and at the same time increase cost-efficiency. The proposal is based on the S-base cash flow tax, where transactions within the corporate sector are not at all taxable and only transactions be-tween shareholders and corporations are subject to tax. In contrast to existing S-base cash flow tax systems, tax deductibility of investments is deferred. Rather, the acquisition costs and capital endowments are compounded at the capital market rate and are set off against fu-ture capital gains. Dividends and withdrawals are fully taxable at the shareholder level. Be-cause of the similarities to the Allowance for Corporate Equity (ACE) tax our proposal is called Allowance for Shareholder Equity (ASE tax). The ASE tax exhibits the same neutrality properties as the traditional cash flow tax. More-over, the compounded inter-temporal credit method ensures that it is neutral with respect to the decision between domestic and foreign investment. To increase acceptance of the ASE tax, current taxpayers' documentation requirements will be reduced rather than extended. Our proposal is shaped in a way that it could be realized in a single EU country or in all member states of the EU.
Keywords: 330; Körperschaftsteuer; Cash-Flow-Steuer; Aktionäre; Steuerbegünstigung; EU-Steuerrecht; Besteuerungsgrundsatz; EU-Staaten